2012
DOI: 10.1093/jjco/hys001
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of MicroRNA-210 is an Independent Factor Indicating a Poor Prognosis in Japanese Triple-negative Breast Cancer Patients

Abstract: Objective: MicroRNAs have emerged as a new class of non-coding genes involved in regulating cell proliferation, differentiation and viability. Recent studies have identified miR-210 as one of a set of hypoxia-regulated microRNAs and demonstrated a direct regulatory role of HIF-1 alpha for its transcription. Here, we assessed miR-210 expression in Japanese triplenegative breast cancers and determined its clinical significance. Methods: TaqMan MicroRNA assays for miR-210 expression were performed on 161 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 35 publications
3
71
0
2
Order By: Relevance
“…Expression of miR-210 (in combination or not with the other hypoxamiRs discussed next) could help select patients at a high clinical risk, as it has been linked to aggressiveness in breast cancer, and, in particular, in the therapeutically challenging ''triple negative'' (estrogen receptor -ve/progesterone receptorve/human epidermal growth factor receptor 2 -ve) subgroup. In a study of Japanese patients with triple negative breast cancer, patients whose breast cancers showed low miR-210 expression experienced significantly better diseasefree and overall survival than those with high miR-210 expression (158). The impact of miR-210 on the efficacy of various types of therapy may, of course, vary.…”
Section: Mir-210: Candidate Cancer Biomarkermentioning
confidence: 99%
“…Expression of miR-210 (in combination or not with the other hypoxamiRs discussed next) could help select patients at a high clinical risk, as it has been linked to aggressiveness in breast cancer, and, in particular, in the therapeutically challenging ''triple negative'' (estrogen receptor -ve/progesterone receptorve/human epidermal growth factor receptor 2 -ve) subgroup. In a study of Japanese patients with triple negative breast cancer, patients whose breast cancers showed low miR-210 expression experienced significantly better diseasefree and overall survival than those with high miR-210 expression (158). The impact of miR-210 on the efficacy of various types of therapy may, of course, vary.…”
Section: Mir-210: Candidate Cancer Biomarkermentioning
confidence: 99%
“…Several lines of clinical studies have indicated that increased levels of miR-210 are related to poor clinical prognosis of breast and pancreatic cancers [164, 165]. The high levels of miR-210 are also identified in lymphoma and lung cancer patients [166168].…”
Section: The Role Of Mirnas In the Regulation Of Ros Productionmentioning
confidence: 99%
“…Functional studies performed in cancer ce ll lines or animal models of various cancers suggest that, miRNAs can function as tumor suppressors, oncogenes, and regulate cancer pathways (Farazi et al, 2011). Aberrant expression of specific miRNAs has been reported in many tumor types 1 such as CRC, breast cancer, cervical cancer, non-small cell lung cancer, ovarian cancer and bladder cancer as well as being associated with patients' survival data, metastasis, and other clinicopathological factors (Toyama et al, 2012;Wan et al, 2012;Shen et al, 2013;Wang et al, 2013;Xiao et al, 2013;Liu et al, 2014;Xu et al, 2014). A previous study showed that miR-32 expression was upregulated in CRC tissues, and high expression was significantly correlated with the tumor stage, distal metastases and poor prognoses (Wu et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%